Pengaruh Ekstrak Daun Jeruju (Acanthus ilicifolius) terhadap Penurunan Kadar LDL Darah pada Tikus Putih (Rattus norvegicus) Jantan Galur Wistar Diabetes yang Diinduksi Aloksan - Anggita Saraswati; Irmawati M. Dikman; Retno Budiarti (Oceana Biomedicina Journal, 2020)
Background : DM is a chronic disease that has long-term complications. Alloxan is a fast way to produce experimental diabetic (hyperglycemic) in animal experiments related to elevated LDL. Jeruju (Acanthus ilicifolius) is a low-growth herbaceous plant that easily grows containing secondary metabolites such as Alkaloids, Saponins, Flavonoids, Terpenoids, and Phenols. Objective : To determine the effect of jeruju leaf extract on the decrease in blood levels of LDL of male Wistar rat (Rattus norvegicus) induced Alloxan.Methods : This research is an experimental laboratory type with Post Test Only Control Group Design. The sample using 24 rats, which were divided into 3 groups: negative control group (K-) were given standard feed; positive control group (K +) induced alloxan 120 mg/kgBW on 1st day; the treatment group (P) induced alloxan 120 mg/kgBW on 1st day and was given jeruju leaf extract 67.2 mg/kgBW on 5th-14thday. The 15th day a blood sample was taken to determine LDL levels.Result : The results of One-Way ANOVA test showed an insignificant mean difference (p = 0.270) in LDL level of K- ( = 9.75 mg/dl) and the K+ ( = 11.38 mg/dl ). Insignificant mean difference (p = 0.270) in P ( = 9 mg/dl) with blood LDL levels in theK+ ( = 11.38 mg/dl) and the K- ( = 9, 75 mg/dl).Conclusion : Giving alloxan can increase blood levels of LDL and administration of jeruju leaf extract can reduce blood levels of LDL in experimental animals but not statistically significant.